2004
DOI: 10.4049/jimmunol.173.11.6547
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Insights on Human NK Cells’ Immunological Modalities Revealed by Gene Expression Profiling

Abstract: As part of the innate immune system, human NK cells play a critical role early in the systemic host defense against pathogens and tumor cells. Recent studies suggest a more complex view of NK cell behavior, as different functions and tissue localizing capabilities seem to be preferentially assigned to distinct subpopulations of NK cells, CD56dimCD16+ or CD56brightCD16−. In this study, we used oligonucleotide microarrays to compare the expression profile of ∼20,000 genes in three NK cell subpopulations: periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
149
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(159 citation statements)
references
References 72 publications
10
149
0
Order By: Relevance
“…In addition, the measurement of antioxidant ability of cellular lysates from CD56 dim and CD56 bright NK cells lends further support to the notion that differences in antioxidative function could explain the difference in sensitivity to H 2 O 2 between these two NK subsets. Recently, expression of genes in CD56 dim CD16 ϩ and CD56 bright CD16 Ϫ NK cell subsets was analyzed using a gene array approach (44). Several genes found to be differentially expressed between CD56 dim and CD56 bright NK cells may be candidate antioxidants, as inferred from this study.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, the measurement of antioxidant ability of cellular lysates from CD56 dim and CD56 bright NK cells lends further support to the notion that differences in antioxidative function could explain the difference in sensitivity to H 2 O 2 between these two NK subsets. Recently, expression of genes in CD56 dim CD16 ϩ and CD56 bright CD16 Ϫ NK cell subsets was analyzed using a gene array approach (44). Several genes found to be differentially expressed between CD56 dim and CD56 bright NK cells may be candidate antioxidants, as inferred from this study.…”
Section: Discussionmentioning
confidence: 68%
“…Both MHC II molecules were significantly upregulated on NK cells, and HLA-DR expression was upregulated to the greatest extent on the CD56 bright CD16 2 NK cell subset (data not shown). Expression of MHC II molecules on human NK cells as mRNA and protein was reported (67,68) but not previously shown to be upregulated by lipopeptide or a viral pathogen, although similar lipopeptides induce maturation and upregulate MHC II on DCs (71).…”
Section: Discussionmentioning
confidence: 93%
“…NK cells can mature DCs and induce the Th1 transcription factor T-bet in CD4 T lymphocytes through IFN-g production (65,66), both of which promote Th1 responses. Hanna et al (28) reported that NK cells (especially the CD56 bright CD16 2 subset) activated by PHA and IL-2 can present Ag, and they defined distinct proteomic and genomic profiles of the two NK cell subsets (67,68).…”
Section: Discussionmentioning
confidence: 99%
“…CD16 + /CD56 + NK cells were cultured in medium alone or stimulated with IL-2 + IL-15 before transcriptional profiling by Amersham CodeLink Human 20K I spotted cDNA arrays (GEO accession no. GSE1511) (52). CD3 + T lymphocytes activated with antibodies to CD3 + CD28 were exposed to norepinephrine or vehicle before transcriptional profiling by Affymetrix HuGene FL high-density oligonucleotide arrays (53).…”
Section: Methodsmentioning
confidence: 99%